2004
DOI: 10.1007/s00406-004-0556-4
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone plasma levels, clinical response and side–effects

Abstract: The major finding was that responders to risperidone treatment had significantly lower blood levels of risperidone and 9-OH risperidone than patients who did not respond to the treatment despite administration of similar oral doses. The observed CYP2D6 polymorphisms did not contribute to altered clinical efficacy, but affected risperidone to 9-OH-risperidone ratios. Increased plasma levels of the active moiety in patients with longer illness may represent general aging effects. Conversely, the observed higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 48 publications
6
75
1
8
Order By: Relevance
“…In recent studies, it was observed that CYP2D6 did not predict response to risperidone, but predicted metabolic ratios and side effects. [62][63][64] No association was found between CYP2D6 PM variants and clozapine response. 65 However, small adjustments of therapeutic doses of clozapine are recommended according to CYP2D6 genotypes, suggesting that these enzymes are only minor pathways for clozapine metabolism.…”
Section: Pharmacokinetic Factorsmentioning
confidence: 97%
“…In recent studies, it was observed that CYP2D6 did not predict response to risperidone, but predicted metabolic ratios and side effects. [62][63][64] No association was found between CYP2D6 PM variants and clozapine response. 65 However, small adjustments of therapeutic doses of clozapine are recommended according to CYP2D6 genotypes, suggesting that these enzymes are only minor pathways for clozapine metabolism.…”
Section: Pharmacokinetic Factorsmentioning
confidence: 97%
“…Ten studies were interested in the relationship between efficacy and CYP2D6 [90][91][92][93][95][96][97][98][99] or CYP1A2. 94 A wide variety of outcomes were considered across the studies but no two studies measured outcomes in exactly the same way.…”
Section: Clinical Validitymentioning
confidence: 99%
“…This gene is considered to be highly polymorphic. We discussed four genetic variants involved in differences in treatment responses in various populations ( • PMs tend to accumulate higher drug levels in blood, and theoretically, require lower doses to achieve therapeutic effects (Kakihara et al [21], n=136; Riedel et al [22], n=82)…”
Section: Cyp2d6mentioning
confidence: 99%
“…Thus, there is a lower dose requirement to attain a therapeutic effect for PMs [21,22]. In contrast, ultra rapid metabolizers (UMs) are needed in higher doses to produce a therapeutic effect [23].…”
Section: Cyp2d6mentioning
confidence: 99%